DESIGN AND IMPLEMENTATION OF AN DYNAMIC IOT CLOUD BASED PROCESSING PLATFORM - Gurujukota Ramesh Babu; Phaneendra Varma Chintalapati; Pokkuluri Kiran Sree; A.V.S. Asha; G. Sujatha; K. Soni Sharmila (Proceedings on Engineering Sciences)
The Internet of Things (IoT) is a pair of technologies which can connect everything from everyday objects to more complex connected devices. The IoT model is continues to increases end-users owned devices. Adoption of smart devices for the IoT, including sensors are growing rapidly. Therefore, storing and processing the amount of data generated on local platforms is becoming increasingly difficult. The scalability of Cloud Computing (CC) offers solutions for this issue. CC makes resources available to users at low cost. However, platform-independent techniques for collecting sensor data and sending it to the cloud are not widely available. This framework represents a cloud-based platform for observing, collecting, and processing data from smart devices. The analysis presents that the detected requirements are data gathering and processing. Hence this analysis achieves best results in terms of security, accuracy, cost and processing time.